Free Cash Flow and Profitability in Indonesian Energy Companies - Amrie Firmansyah; Nafis Dwi (Universitas Prasetiya Mulya, 2025)
This study aims to analyze the relationship between free cash flow (FCF) and firm profitability in the energy sector in Indonesia. Using a quantitative approach and panel regression method, this study evaluates data from 978 annual observations of energy companies over the period 2002-2023. The analysis shows that FCF generally has a significant negative effect on profitability, both short-term (ROA, ROE) and long-term (LTROA, LTROE). This negative effect is most pronounced in the middle quantiles of the firm performance distribution, supporting the argument in agency theory that free cash accumulation without adequate supervision may trigger opportunistic managerial behavior and inefficient investment. In contrast, at the highest quantile, the effect of FCF tends to be insignificant, indicating that high-performing firms are able to manage FCF more optimally. This finding emphasizes the importance of strengthening corporate governance mechanisms to direct FCF allocation to productive investments and improve long-term profitability.